Prognosis of adult obstructive hypertrophic cardiomyopathy patients with different morphological types after surgical myectomy. (12th February 2018) - Tang, Bing; Song, Yunhu; Cui, Hao; Ji, Keshan; Yu, Qinjun; Zhu, Changsheng; Zhao, Shihua; Wang, Shuiyun
Abstract: OBJECTIVES: This study aims to assess the impact of morphological type on the prognosis of obstructive hypertrophic cardiomyopathy patients who underwent myectomy. METHODS: We recruited 469 obstructive hypertrophic cardiomyopathy patients refractory to medicinal treatment who have undergone surgical myectomy at a nationwide referral centre. All patients were divided into 3 groups based on the morphological classification of left ventricular hypertrophy and were followed up by telephone every year. The primary end-points were sudden cardiac death, aborted sudden cardiac death and death due to heart failure or stroke. The secondary end-points were non-fatal cardiovascular events. RESULTS: Typical hypertrophy limited to the basal septum, hypertrophy of the whole ventricular septum and hypertrophy that involved the whole left ventricle were presented in 248 (52.9%), 141 (30.1%) and 80 (17.0%) patients, respectively. During the follow-up of 2.5 ± 1.4 years after myectomy, 10 (2.1%) and 43 (9.2%) patients met the primary end-point and secondary end-points, respectively. The maximal thickness of the ventricular septum, the left ventricular mass and the presence of extensive late gadolinium enhancement were lower in patients with hypertrophy limited to the basal septum than in other patients. Patients with the basal septum hypertrophy showed better survival after myectomy compared with other patients. For the secondary and composite end-points, there was no significant difference between the 3 groups. CONCLUSIONS: Patients with hypertrophy limited to the basal septum represented a special clinical subtype of obstructive hypertrophic cardiomyopathy showing better clinical outcomes, while diffuse hypertrophy of the ventricular septum and free wall indicated lower survival after surgical myectomy.